Death certification errors in medical certificates of cause of death related to COVID-19 disease - Patil, Amit; Singh, Nilabh Prasad (International Journal Of Community Medicine And Public Health, 2022)
Background: In the case of public health emergency scenarios, mortality surveillance done by analyzing medical certificates of cause of death (MCCDs) provides accurate morbidity and mortality data. Precise death certification in the novel coronavirus disease 2019 deaths is critical to understanding the magnitude and advancement of the pandemic. Inaccurate death certificates may cause underreporting or overwhelming reporting of COVID-19 deaths. Methods: The aim of the study was to analyse the MCCDs issued by the institute where the cause of death was attributed to or associated with the COVID-19 infection for certification errors. 729 MCCDs issued in COVID-19 deaths were audited primarily for their formal correctness and completeness and errors, using categories previously reported with some minor modifications. The study did not include analyzing the medical and hospital records of the deceased for the factual correctness of these MCCDs. Results: All types of major and minor certification errors were observed. Incomplete MCCDs were observed in 697 (95.61%) cases. 691 MCCDs (94.8%) were having either major or minor or both types of errors. Abbreviations were used in the MCCDs in 65.29% of cases while improper sequencing of the causes of death was observed in 52.92% of cases. Wrong terminologies like “COVID”, “COVID pneumonia”, “COVID +ve”, and “coronavirus” were used instead of the standard terminology. Conclusions: The lack of completeness and accuracy in writing the causes of death related to COVID-19 indicates a problem faced by the certifying doctors in analyzing them, especially in the early days of the pandemic. Both major and minor errors were identified in this study.